Formulation and Evaluation of Effervescent Granules Ethanol Extract of Andaliman Fruit (Zanthoxylum acanthopodium DC) with Combination of Citric Acid-Tartaric Acid and Sodium Bicarbonate - Olivia Laurent; Tia Triyanti; Dika Suranda; Chiuman, Linda (HM Publisher, 2023)
The combination of citric acid-tartaric acid and sodium bicarbonate in effervescent granules has an important role in providing an effervescent effect. Citric acid and tartaric acid are organic acids that can react with sodium bicarbonate when they come in contact with water. This reaction results in the release of carbon dioxide gas, which has a splitting effect and makes the effervescent granules dissolve rapidly in water. Research on the formulation and evaluation of effervescent granules of andaliman fruit ethanol extract with a combination of citric acid-tartaric acid and sodium bicarbonate aims to optimize the stability, solubility, and release of the active ingredients from the granules. This study is an experimental research. Evaluation of effervescent granules is carried out in the form of an organoleptic test. This test can be observed directly from the granules through the shape, color, aroma, and taste produced. Granular specific gravity test, namely real specific gravity, compressed specific gravity, flow rate test, angle of repose test, and compressibility. Tests for dispersion time and pH tests were carried out in this study. FI, FII, and FIII meet the requirements of the organoleptic test, compressibility, flow rate, angle of repose, dispersion time, and pH test. Even though the pH test for the 3 formulas found a pH range of 5.5 to 5.7, but still declared to meet the requirements because it is still close to neutral pH. The best influence on the physical properties of granules effervescent, namely in FIII, as seen in the organoleptic test, flow rate, angle of repose, and dispersion time.